A Grammatical Approach to the Modeling of an Autonomous Robot - López-García, Gabriel; Gallego-Sánchez, A. Javier; Dalmau-Espert, J. Luis; Molina-Carmona, Rafael; Compañ-Rosique, Patricia (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Virtual Worlds Generator is a grammatical model that is proposed to define virtual worlds. It integrates the diversity of sensors and interaction devices, multimodality and a virtual simulation system. Its grammar allows the definition and abstraction in symbols strings of the scenes of the virtual world, independently of the hardware that is used to represent the world or to interact with it. A case study is presented to explain how to use the proposed model to formalize a robot navigation system with multimodal perception and a hybrid control scheme of the robot. The result is an instance of the model grammar that implements the robotic system and is independent of the sensing devices used for perception and interaction. As a conclusion the Virtual Worlds Generator adds value in the simulation of virtual worlds since the definition can be done formally and independently of the peculiarities of the supporting devices.
Keywords: autonomous robots; virtual worlds; grammatical models; multimodal perception; IJIMAI